Altered muscle electrical tissue properties in a mouse model of premature aging. Issue 6 (30th October 2019) - Clark‐Matott, Joanne; Nagy, Janice A.; Sanchez, Benjamin; Taylor, Rebecca; Riveros, Daniela; Abraham, Neeta A.; Simon, David K.; Rutkove, Seward B.
Abstract: Introduction: Improved methods are needed to detect and quantify age‐related muscle change. In this study we assessed the electrical properties of muscle impacted by acquired mitochondrial DNA mutations via the PolG mouse, which exhibits typical age‐associated features, and the impact of a potential therapy, nicotinamide mononucleotide (NMN). Methods: The gastrocnemii of 24 PolG and 30 wild‐type (WT) mice (8 PolG and 17 WT treated with NMN) were studied in an electrical impedance‐measuring cell. Conductivity and relative permittivity were determined from the impedance data. Myofiber cross‐sectional area (CSA) was quantified histologically. Results: Untreated PolG mice demonstrated alterations in several impedance features, including 50‐kHz relative permittivity and center frequency. A potential effect of NMN was also observed in these parameters in PolG but not WT animals. Impedance values correlated with myofiber CSA. Discussion: Electrical impedance is sensitive to myofiber features considered characteristic of aging and to the impact of a potential therapy.